Penerapan Model Project-Based Learning Berbantuan Media Konkret Stik dan Plastisin Untuk Meningkatkan Pemahaman Konsep Bangun Datar Pada Siswa Kelas IV Sekolah Dasar - Yeni Amalia Mulyawati; Aisyah Berliana Budianti; Nabela Aulya Rosalinda Asri; Anggun Anggelica; Danis Ivi; Selfia Ayunengtias (Universitas PGRI Madiun, 2026)
Understanding geometric shapes is one of the essential competencies in primary school mathematics. However, abstract concepts often pose difficulties for fourth-grade students. This study aims to describe the implementation of the Merdeka, Curriculum teaching module focused on flat shapes (geometry) using Project-Based Leaming (PBL) assisted by concrete media such as sticks and plasticme (clay). The method used is a descriptive qualitative analysis based on classroom learning design and implementation framework. The research subjects were fourth-grade students at SDN Islam Terpadu Badrussalam with a total of 20 students. The leaming activities integrated the Pancasila, Student Profile, emphasizing critical thinking and mutual cooperation. The results demonstrated that the utilization of hands-on concrete media facilitated students in identifying, defining, and differentiating the characteristics of geometric shapes, such as triangles, squares, rectangles, trapezoids, parallelograms, and kites. Active collaboration during the project compilation enhanced students' communication and analysis skills, making the geometry leaming layout more meaningful and contextual